Kajian Arsitektur Kontekstual sebagai Dasar Perancangan Pusat Informasi Wisata Kabupaten Pacitan - Yoni Prasetyo; Endah Tisnawati (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
Pacitan Regency have various extraordinary tourism potentials. Nowadays, the tourims marketing activities has only been carried out through makeshift facilities at the Pacitan Regency Tourism Office in simple manner. This study discusses the design of a tourist information center in Pacitan Regency using the contextual architectural approach. Implementataion on design adapted to sustained contextual architectural theories on problems is presented. Adjustments to modules, typologies, and the landscape of surrounding buildings, which are still lacking in attention to new buildings, as well as aspects of climatology, culture, and building user problems, which are still largely neglected in existing buildings, so this needs to be adjusted to the design of tourist information centers using the approach of contextual architecture.The analysis results concluded that the contextual architectural approach could adjust and solve existing problems and potential related to the design of the tourist information center.